Alkaline water electrolysis membrane and its preparation process and alkaline water electrolysis device

By using a porous hydrophilic layer composed of polymers and inorganic hydrophilic particles in the alkaline water electrolytic separator, combined with the design of the porous carrier, the problem that existing separators are difficult to achieve both high airtightness and low resistance is solved, and a more efficient electrolysis process and a purer product are achieved.

CN119753751APending Publication Date: 2025-04-04HANGZHOU COBETTER FILTRATION EQUIPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411992082.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing alkaline water electrolytic separators are difficult to achieve both high airtightness and low resistance, resulting in high electrolytic energy consumption and low product purity.

Method used

An alkaline water electrolytic separator formed by a porous hydrophilic layer composed of polymer and inorganic hydrophilic particles is formed by combining a porous support. The porous hydrophilic layer is at least partially penetrated into the porous structure of the porous support to ensure that the separator has good ion conduction ability and airtightness.

Benefits of technology

The high airtightness and low resistance of alkaline water electrolytic separators are achieved, which reduces electrolytic energy consumption, and improves the purity of hydrogen and oxygen, avoids gas crossover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753751A_ABST
    Figure CN119753751A_ABST
Patent Text Reader

Abstract

The present invention relates to an alkaline water electrolysis diaphragm and a method and application thereof, wherein the alkaline water electrolysis diaphragm comprises a porous carrier and a porous hydrophilic layer arranged on both sides of the porous carrier, wherein the porous hydrophilic layer comprises a high molecular polymer and inorganic hydrophilic particles, and the porous hydrophilic layer at least partially penetrates into the pore structure of the porous carrier; the thickness of the alkaline water electrolysis diaphragm is 150 μm-600 μm, and the maximum diameter-thickness ratio is 20 kPa / 100 μm-200 kPa / 100 μm, and the maximum diameter-thickness ratio is the ratio of the IPA bubbling point corresponding to the maximum pore size of the diaphragm to the thickness of the diaphragm; the porosity of the alkaline water electrolysis diaphragm is 45%-75%, and the water contact angle is less than or equal to 80°. The alkaline water electrolysis diaphragm has both high air tightness and low resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to an alkaline water electrolysis membrane and a preparation process thereof, and an alkaline water electrolysis device. Background Art

[0002] The cost reduction of renewable energy such as wind and solar energy has led to a rapid increase in the share of electricity generated by these renewable energy sources. However, renewable energy such as wind and solar energy are also unpredictable, so a scalable energy storage system is often required. Hydrogen energy has outstanding advantages such as high energy density, high calorific value, high conversion efficiency, flexibility and environmental friendliness. It is currently an ideal energy carrier. The continuous reduction in the cost of renewable energy also makes the energy storage method of hydrogen production through electrolysis highly competitive.

[0003] In the process of electrolytic hydrogen production, the typical characteristics of proton exchange membrane (PEM) electrolytic hydrogen production are high current density and short start-up time, but it requires precious metals such as platinum or iridium as catalysts for bipolar plates, which greatly limits the reduction of electrolytic hydrogen production costs; polymer anion exchange membrane (AEM) shows good electrolytic performance, but AEM has poor stability in alkaline environments and easily reacts with hydroxide ions, causing the anion exchange group to degrade and fail. Compared with PEM and AEM, the alkaline electrolysis process has good compatibility with non-precious metal catalysts, high maturity, high chemical stability, and more importantly, its cost is lower, which is more attractive than PEM and AEM electrolytic hydrogen production technologies.

[0004] However, it is difficult for diaphragms used in alkaline electrolysis to achieve both good gas cross-protection and low resistance. This is because the large pores of the diaphragm are more conducive to the penetration of electrolytes into the pores to form ion migration channels, reducing resistance and thus reducing electrolysis energy consumption. However, the large pores will also reduce the gas barrier effect, easily leading to cross-mixing of hydrogen and oxygen obtained by electrolysis, which affects the purity of the product on the one hand and poses a safety hazard on the other.

[0005] Therefore, there is an urgent need to provide an alkaline water electrolysis diaphragm having both high air tightness and low resistance. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide an alkaline water electrolysis diaphragm and a method and application thereof, wherein the alkaline water electrolysis diaphragm has both high air tightness and low resistance.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, the present invention provides an alkaline water electrolysis membrane, which adopts the following technical solution:

[0009] An alkaline water electrolysis diaphragm comprises a porous carrier and a porous hydrophilic layer disposed on both sides of the porous carrier, wherein the porous hydrophilic layer comprises a high molecular polymer and inorganic hydrophilic particles, and the porous hydrophilic layer at least partially penetrates into the pore structure of the porous carrier;

[0010] The thickness of the alkaline water electrolysis membrane is 150μm-600μm, and the maximum thickness ratio is 20kPa / 100μm-200kPa / 100μm, and the maximum thickness ratio is the ratio of the IPA bubbling point corresponding to the maximum pore size of the membrane to the thickness of the membrane; the porosity of the alkaline water electrolysis membrane is 45%-75%, and the water contact angle is less than or equal to 80°.

[0011] By adopting the above technical scheme, in the membrane structure of the alkaline water electrolysis diaphragm provided by the present invention, along the film thickness direction, it can be clearly seen that the diaphragm includes a porous carrier and a porous hydrophilic layer arranged on both sides of the porous carrier. In the alkaline electrolysis process, on the one hand, the alkaline water electrolysis diaphragm needs to ensure the rapid migration of hydroxide ions and has a large number of ion migration channels. On the other hand, the alkaline water electrolysis diaphragm also needs to isolate hydrogen and oxygen from mixing to avoid gas crossing and has a lower air permeability. However, it is often difficult to have both, because a large number of ion migration channels often also become channels for gas movement, resulting in gas crossing problems, which is unacceptable; on the contrary, although the gas crossing problem can be reduced, higher resistance will lead to a significant increase in electrolysis energy consumption.

[0012] Therefore, the alkaline water electrolysis membrane of the present application is composed of a porous hydrophilic layer composed of high molecular polymers and inorganic hydrophilic particles, and the porous hydrophilic layer at least partially penetrates into the pore structure of the porous carrier. The porous carrier plays a supporting and strengthening role, reducing the possibility of the membrane being damaged by gas impact, equipment vibration, etc. during the electrolysis process.

[0013] The polymer is blended with inorganic hydrophilic particles, where the polymer, as a film-forming component, ensures that the diaphragm is formed and well attached to the porous carrier. On the other hand, the polymer serves as the basis for the adhesion and physical intercalation of the inorganic hydrophilic particles, and can keep the inorganic hydrophilic particles in the diaphragm to prevent them from falling off. Due to the weak hydrophilicity of the polymer, the addition of inorganic hydrophilic particles is necessary. On the one hand, the addition of inorganic hydrophilic particles can improve the wettability of the diaphragm and the electrolyte, improve the hydrophilicity of the diaphragm, and promote the conduction of the electrolyte in the positive and negative electrodes, thereby reducing the resistance of the diaphragm; on the other hand, the inorganic hydrophilic particles can produce a hydrogen bond network, so they have good intrinsic OH -Conductivity, on the basis of ion transfer by electrolyte, further obtains better ion conductivity; in addition, since the size of inorganic hydrophilic particles remains unchanged before and after membrane formation, it can generate additional pore structures between particles on the basis of the pore structure generated by the polymer itself, thereby obtaining a large number of microporous channels; finally, the better the hydrophilicity of the diaphragm, the less likely it is to adsorb bubbles on the surface, and the location where the bubbles exist becomes an actual open circuit because it cannot pass through the electrolyte, thereby increasing resistance.

[0014] In short, the inorganic hydrophilic particles and the high molecular polymer can form a membrane with good ion conductivity and preliminary gas cross-prevention ability, so that it is suitable for alkaline water electrolysis applications. It should be noted that although the membrane in this application is mainly used for alkaline water electrolysis to produce hydrogen, it can also be used for electrolysis of hydrogen and chlorine in the chlor-alkali industry.

[0015] As mentioned above, if the diaphragm wants to obtain lower resistance, it is beneficial to introduce a larger pore flow channel structure, but this is not conducive to preventing gas crossover, and vice versa. Therefore, high air tightness and low resistance are generally difficult to achieve at the same time. However, the inventors of the present application found that when the thickness of the alkaline water electrolysis diaphragm is 150μm-600μm, the maximum diameter-to-thickness ratio is 20kPa / 100μm-200kPa / 100μm, the porosity is 45%-75%, and the water contact angle is less than or equal to 80°, the alkaline water electrolysis diaphragm has both high air tightness and low resistance.

[0016] This may be because, under the conditions of a thickness of 150μm-600μm and a maximum diameter-to-thickness ratio of 20kPa / 100μm-200kPa / 100μm, the alkaline water electrolysis membrane of the present application has a special small pore size and a porosity of 45%-75%. At this time, although the pore size of the membrane is small, the pores are densely arranged and inorganic hydrophilic particles are distributed in the pores. The distance between the hydrophilic points is small, so the hydrophilic points are connected in series with each other, and the area of ​​the high molecular polymer between the pores is small, which is not easy to adsorb bubbles, and the hydrophilic sites are connected to each other, which can also produce a better shielding effect on the gas.

[0017] Specifically, on the basis of the diaphragm thickness of 150μm-600μm, its maximum diameter-to-thickness ratio is not less than 20kPa / 100μm, which means that under unit thickness, the diaphragm of the present application has a larger IPA bubbling point, and the IPA bubbling point often corresponds to the largest pore flow channel structure in the diaphragm. Therefore, the maximum diameter-to-thickness ratio of not less than 20kPa / 100μm means that even the largest pore flow channel structure in the diaphragm is smaller in size. In addition, unlike general cognition, it is generally believed that the size of water molecules is larger than that of gas molecules. Therefore, water permeability often means that gas can permeate. However, since the application scenario of the diaphragm in the present application is electrolysis, the higher temperature during electrolysis (such as 70-90°C) makes the dissolved gas in the electrolyte less and basically exists in the form of larger bubbles. Therefore, the maximum diameter-to-thickness ratio is not less than 20kPa / 100μm and is combined with inorganic hydrophilic particles with good hydrophilicity, which greatly reduces the possibility of these bubbles adhering to and passing through the pore flow channel, and thus has good air tightness and avoids gas crossover. Of course, the maximum diameter-to-thickness ratio of the diaphragm should not be too large. For example, within the thickness range of the present application, it should not be greater than 200 kPa / 100 μm. This is because, after the size of the pore channel is reduced to a certain extent, its ability to prevent gas crossover is already very good. Further reducing its size will have a limited effect on the ability to prevent gas crossover, and there is a marginal diminishing effect. However, further reducing the size of the pore channel will further increase the difficulty of electrolyte wetting, resulting in an increase in resistance.

[0018] On the basis of the maximum diameter-to-thickness ratio being not less than 20kPa / 100μm, the porosity of the diaphragm in the present application is not less than 45%. The combination of the two means that although the size of the pore flow channel of the diaphragm in the present application is small, it has a high porosity, which indicates that there are a large number of small-sized pore flow channels in the diaphragm, and a large number of small-sized pore flow channels are interconnected to form an intricate three-dimensional flow channel. Its small size and winding structure can greatly reduce the possibility of gas crossing, but a large number of interconnected three-dimensional flow channels provide an optional path for the ion transfer process, especially the shorter path can significantly reduce the resistance of lithium ion transfer (the vertical transmembrane movement of ions is the shortest path and also has lower resistance), thereby obtaining a lower resistance. Of course, the porosity should not be too high. For the diaphragm with a thickness of 150μm-600μm and a maximum diameter-to-thickness ratio of not less than 20kPa / 100μm in the present application, its porosity should not be higher than 75%. Although this can further reduce the resistance, it inevitably leads to a decrease in the hydrophilicity of the diaphragm, resulting in an increase in the possibility of bubble attachment and permeation. For this reason, the diaphragm in the present application has a water contact angle of no more than 80°, which indicates that the diaphragm has relatively good hydrophilicity.

[0019] In addition, in the process of producing hydrogen by electrolysis of water, the energy used is often unstable (such as photovoltaic power supply, wind power, etc.), and the gas produced by electrolysis also fluctuates, which is more likely to produce uneven impact; and due to the circulation of the electrolyte, the inevitable vibration of the equipment operation, etc., the diaphragm will be in a vibrating and pressure-unbalanced working condition for a long time. Whether from the perspective of the mechanical strength of the diaphragm or from the perspective of the local air permeability of the diaphragm, a structure with small and evenly distributed pores can reduce stress concentration, avoid local damage, and is more conducive to achieving good anti-gas cross performance during long-term use.

[0020] It is understood that the thickness of the alkaline water electrolysis membrane includes but is not limited to any point value of 150μm, 200μm, 300μm, 400μm, 500μm, 600μm or any range value between the two; the maximum diameter-to-thickness ratio includes but is not limited to any point value of 20kPa / 100μm, 50kPa / 100μm, 100kPa / 100μm, 120kPa / 100μm, 150kPa / 100μm, 200kPa / 100μm or any range value between the two, and the unit of thickness is μm, and the unit of IPA bubble point is kPa. The porosity includes but is not limited to any point value of 45%, 50%, 55%, 60%, 65%, 70%, 75% or any range value between the two; the water contact angle includes but is not limited to any point value of 30°, 40°, 50°, 60°, 70°, 80° or any range value between the two.

[0021] In this application, the thickness of the diaphragm can be directly measured by equipment such as a thickness gauge, a spiral micrometer, etc., or by obtaining a magnified image of the cross section of the diaphragm through equipment such as an electron microscope, an ultra-depth microscope, etc., and then detecting and obtaining it. Of course, the other conventional test methods in this field are also acceptable. In this application, the IPA bubble point is measured by a bubble point tester using a diaphragm as a sample, wherein the test liquid is IPA (isopropanol) and the test gas is nitrogen or air. The porosity is measured by using a diaphragm as a sample, and the mass of the diaphragm under dry and water-wetting conditions is measured respectively, and the water absorption mass of the diaphragm is obtained to obtain the pore volume in the diaphragm, and the porosity is calculated by the ratio of the pore volume to the diaphragm volume. Of course, the other conventional test methods in the field are also acceptable. The water contact angle is taken as a sample by a water contact angle tester to shoot an optical image of deionized water dripping on the surface of the diaphragm, and the tangent angle between its gas-liquid interface and the liquid-solid interface is measured to obtain the water contact angle data.

[0022] The high molecular polymer described in the present application includes but is not limited to at least one of polysulfone, polyethersulfone and polyphenylsulfone.

[0023] The inorganic hydrophilic particles include, but are not limited to, at least one of zirconium oxide, titanium oxide, bismuth oxide, cerium oxide, magnesium oxide, zirconium hydroxide, titanium hydroxide, bismuth hydroxide, cerium hydroxide, magnesium hydroxide and barium sulfate.

[0024] Optionally, in the pore size-pore volume distribution curve of the alkaline water electrolysis membrane, the abscissa is the pore size and is sorted from small to large, and the ordinate is the change in pore volume under a unit pore size change, and the pore size-pore volume distribution curve satisfies at least one of the following conditions:

[0025] (1) The highest peak is located in the 1nm-10nm pore size region;

[0026] (2) The peak intensity of the highest peak in the pore size region of 10 nm to 100 nm is greater than the peak intensity of the highest peak in the pore size region of more than 100 nm.

[0027] By adopting the above technical solution, the pore size distribution is calculated using the NLDFT method in the BET test and the pore size distribution curve is fitted, so that the pore size distribution of the pore flow channel in the diaphragm can be characterized.

[0028] In the present application, the diaphragm not only has a large number of small-sized pore flow channel structures, but also has the most pore flow channel distribution in the 1nm-10nm pore size region, and the aforementioned maximum diameter-to-thickness ratio is not less than 20kPa / 100μm and the porosity is not less than 45%, indicating that the diaphragm has a high porosity but does not have a large-sized pore flow channel structure, and the size of a large number of pore flow channels is distributed in the 1nm-10nm pore size region. Therefore, the diaphragm of the present application has the characteristics of "small pore size + high pore density". On the one hand, the pore flow channel with an pore size of 1nm-10nm combined with a winding three-dimensional flow channel structure can significantly reduce the possibility of large-sized bubbles generated by electrolysis passing through, and the hydrophilic particles in a large number of small pore structures are interconnected to form a hydrophilic network, which can further avoid bubble attachment and penetration, reduce the electrolysis voltage and improve air tightness; on the other hand, the three-dimensional pore structure formed by a large number of small pores can reduce the path of ion conduction, thereby further optimizing the air tightness and resistance of the alkaline water electrolysis diaphragm. The peak intensity of the highest peak in the pore size region of 10nm-100nm is greater than the peak intensity of the highest peak in the pore size region above 100nm, which means that the number of pore flow channels in the pore size region above 100nm accounts for a small proportion, and there is a possibility of bubble intrusion in these pore flow channels.

[0029] It is worth noting that the IPA bubble point is mainly used to test the size of the largest hole flow channel of the diaphragm. However, considering that the bubble point method is difficult to characterize the distribution of small pores in the diaphragm (gas is more likely to pass through large pores to produce bubbles, and is not easy to pass through small pores), the present application further uses the BET gas adsorption method to test the gas adsorption and desorption data of the diaphragm (nitrogen as the test gas), and uses the NLDFT method to calculate the pore size distribution and fit the pore size distribution curve, because the good permeability and adsorption properties of the gas can well characterize the distribution of small-sized pore flow channels in the diaphragm.

[0030] Optionally, in the pore size-pore volume distribution curve of the alkaline water electrolysis membrane, the peak intensity ratio of the highest peak in the pore size region of 1 nm-10 nm to the highest peak in the pore size region of 10 nm-100 nm is 1.5-10.

[0031] By adopting the above technical solution, the peak intensity ratio of the highest peak in the 1nm-10nm pore size region to the highest peak in the 10nm-100nm pore size region characterizes the distribution of pore channels of different sizes of the diaphragm to a certain extent. In particular, the ratio of the two is not less than 1.5, which means that although a large number of pore channels are concentrated in the pore size region below 100nm, they are more concentrated in the 1nm-10nm pore size region, and the ratio of the two is not more than 10, which means that there are also a large number of pore channels distributed in the 10nm-100nm pore size region. Therefore, the diaphragm in the present application has a large number of pore channels less than 10nm that are difficult for bubbles to enter, and the pore channels in the 10nm-100nm pore size region can greatly improve the ability of the diaphragm to wet the electrolyte to form ion transmission channels, and cooperate with a large number of small-sized pore channels to make the diaphragm have good gas barrier properties and low electrolytic resistance.

[0032] In summary, the alkaline water electrolysis membrane has a rich pore structure, which is beneficial to further improve the air tightness while reducing the resistance. It is understood that the peak intensity ratio of the highest peak in the 1nm-10nm pore size region to the highest peak in the 10nm-100nm pore size region includes but is not limited to any point value among 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any range value between the two.

[0033] Optionally, in the pore size-pore volume distribution curve of the alkaline water electrolysis membrane, the peak intensity ratio of the highest peak in the pore size region of 1 nm-10 nm to the highest peak in the pore size region of 0-1 nm is greater than or equal to 5.

[0034] By adopting the above technical scheme, although the pore channels in the too small pore area can allow gas molecules to penetrate and obtain corresponding pore size data during the BET test, these too small pore structures tend to be formed by high molecular polymers, so the hydrophilicity of their pore walls is slightly poor, and the wettability with electrolytes and the ability to form ion channels after wetting are both weak. Therefore, the proportion of pore channels in the 0-1nm pore size region is preferably controlled to be less, specifically, the peak intensity ratio of the highest peak in the 1nm-10nm pore size region to the highest peak in the 0-1nm pore size region is greater than or equal to 5, so that most of the pore channel structures can play a role in ion transfer and reduce the proportion of invalid pore channels.

[0035] In short, the pore structure mainly distributed in the alkaline water electrolysis membrane is 1nm-10nm in diameter, which reduces the problems of affecting ion channels caused by too small pore structure, and is conducive to improving air tightness while ensuring low resistance. It can be understood that the peak intensity ratio of the highest peak in the 1nm-10nm pore size region to the highest peak in the 0-1nm pore size region includes but is not limited to any point value among 5, 6, 7, 8, 9, 10 or any range value between the two.

[0036] Optionally, the ratio of the SEM median pore size to the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is 0.7-1.2;

[0037] And / or, the surface pores of the alkaline water electrolysis membrane have a pore area percentage of 20%-60% on the surface of the alkaline water electrolysis membrane.

[0038] By adopting the above technical solution, both the IPA bubble point pore size and the BET pore size of the diaphragm are actually indirect pore sizes, which can characterize the pore channel distribution of the entire diaphragm, but cannot reflect the real pore distribution on the surface of the diaphragm. For the diaphragm, the surfaces on both sides are directly in contact with bubbles, face impact, and contact with electrolytes. Therefore, the real pore structure distribution on the two sides has a great influence on the performance of the diaphragm.

[0039] Specifically, on the basis that the diaphragm as a whole has a large number of small-size pore flow channel structures, the diaphragm surface pores in the present application have a non-excessive skewed distribution, which indicates that the pores on the diaphragm surface are neither excessively distributed in small pores nor excessively distributed in large pores. When the average value of the surface pore diameter is greater than its median value (i.e., the ratio of the two is less than 1), it indicates that the pore size data is positively skewed, and the pore size is mainly distributed on the small pore side, and when the average value is less than the median value (the ratio of the two is greater than 1), the pore size data is negatively skewed, and the pore size is distributed on the large pore side. The ratio of the two is controlled to be 0.7-1.2, indicating that the pore structure on the diaphragm surface is more inclined to normal distribution rather than skewed distribution, and for the surface of the diaphragm, although a large number of small pore structures can indeed further avoid gas adsorption on the surface and bubble invasion into the inside of the diaphragm, it also hinders the electrolyte from entering the inside of the diaphragm, and it is difficult to ensure that the diaphragm is fully and quickly wetted, resulting in excessive electrolysis start-up voltage; on the contrary, although the electrolyte is more likely to enter the inside of the diaphragm for full and rapid wetting, the possibility of gas surface adsorption and bubble invasion is also increased.

[0040] In short, the ratio of the SEM median pore size to the SEM average pore size of the surface pores of the alkaline water electrolysis membrane reflects the surface pore distribution of the alkaline water electrolysis membrane. Under certain proportions, the surface pores of the alkaline water electrolysis membrane have more small pores and appropriate large pores, which is conducive to further balancing the airtightness and resistance properties of the membrane. It is understood that the ratio of the SEM median pore size to the SEM average pore size of the surface pores of the alkaline water electrolysis membrane includes but is not limited to any point value of 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or any range value between the two. If the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is larger than the SEM median pore size, it means that the pore size data is positively skewed, that is, the pore size distribution is mainly small pores; if the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is smaller than the SEM median pore size, it means that the pore size data is negatively skewed, that is, the pore size distribution is mainly large pores, which may make it difficult to achieve a balance between the airtightness and resistance performance of the membrane.

[0041] Further optimizing the surface pore area ratio of the alkaline water electrolysis membrane (the total pore area ratio per unit area of ​​the membrane surface) is beneficial to the alkaline water electrolysis membrane to balance high air tightness and low resistance. If the pore area ratio is too low, it means that a large area of ​​the membrane surface is a high molecular polymer with poor hydrophilicity, which can easily lead to bubble adsorption and wettability problems of the membrane; if the pore area ratio is too high, on the one hand, the impact resistance of the membrane surface is weak, and on the other hand, it is difficult to avoid bubbles from invading the inside of the membrane. It is understandable that the surface pores of the alkaline water electrolysis membrane include but are not limited to any point value of 20%, 30%, 40%, 50%, 60% or any range value between the two.

[0042] In the present application, whether it is the surface pore size of the diaphragm or the microscopic morphological parameters such as the surface pore area percentage of the diaphragm, they are all the average data of the surfaces on both sides of the diaphragm, and the surface magnified image of the diaphragm can be obtained by an electron microscope, an ultra-depth of field microscope and other equipment, and the corresponding data can be obtained by manual measurement (such as CAD, nano measure and other software) or automatic measurement (such as image J and other software).

[0043] Optionally, on the surface of the alkaline water electrolysis membrane, the average value of the minimum distance between adjacent pore structures is 100 nm-500 nm.

[0044] By adopting the above technical solution, since the inorganic hydrophilic particles are mainly distributed in the pore structure, controlling the minimum distance between adjacent pore structures is actually controlling the mutual distance between the hydrophilic sites on the surface of the diaphragm. The minimum distance between adjacent pore structures is no more than 500nm, so a relatively dense hydrophilic node network can be formed on the surface of the diaphragm, making it difficult for bubbles to be adsorbed on the surface of the diaphragm. The minimum distance between adjacent pore structures is no less than 100nm, which can reduce the possibility of gas intrusion into a large number of pore structures.

[0045] In short, the spatial distribution of the pore structure is further regulated, the high pore density structure of the alkaline water electrolysis membrane is optimized, and the principle that the high molecular polymer area distributed between the pores is small and it is not easy to adsorb bubbles is utilized, thereby further reducing the resistance of the alkaline water electrolysis membrane. It is understood that on the surface of the alkaline water electrolysis membrane, the average value of the minimum distance between adjacent pore structures includes but is not limited to any point value of 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or any range value between the two, preferably 150nm-350nm.

[0046] Optionally, the ratio of the SEM particle size of the inorganic hydrophilic particles to the average value of the minimum distance between adjacent pore structures is 0.1-1.5.

[0047] By adopting the above technical solution, the smaller the particle size of the inorganic hydrophilic particles, the larger the specific surface area, and the same addition amount can provide a larger amount of hydrophilic surface, but the smaller particle size of the inorganic hydrophilic particles is also more likely to fall off under external impact. By controlling the ratio of the SEM particle size of the inorganic hydrophilic particles to the average value of the minimum distance between adjacent pore structures, when the hydrophilic node network formed on the diaphragm surface is sparse, it can be compensated by introducing small-size inorganic hydrophilic particles with larger specific surface area, thereby further avoiding the adsorption of bubbles on the diaphragm surface. It is worth noting that the nominal particle size of the inorganic hydrophilic particles is not equivalent to the SEM particle size. For example, the nominal particle size D 50The particle size of zirconium dioxide is 0.4-0.7 μm. The SEM image is taken and the particle size of a single zirconium dioxide is measured to be only about 60-70 nm.

[0048] Therefore, further regulating the spatial distribution of the inorganic hydrophilic particles and the pore structure and optimizing the high pore density structure of the alkaline water electrolysis membrane is conducive to further balancing the airtightness and resistance performance of the membrane. It is understood that the ratio of the SEM particle size of the inorganic hydrophilic particles to the average value of the minimum distance between the adjacent pore structures includes but is not limited to any point value of 0.1, 0.2, 0.5, 1, 2, 3, 4, 5 or a range value between any two, preferably 0.2-3.

[0049] Similarly, in the present application, the actual measured size of the inorganic hydrophilic particles can be obtained by obtaining an enlarged image of the surface of the diaphragm through an electron microscope, an ultra-depth of field microscope, etc., so that the boundaries of the inorganic hydrophilic particles can be clearly seen, and the corresponding data can be obtained by manual measurement (such as CAD, nano measure and other software) or automatic measurement (such as image J and other software).

[0050] Optionally, the ratio of the PMI average pore size of the alkaline water electrolysis membrane to the thickness of the alkaline water electrolysis membrane is less than or equal to 10 nm / 100 μm.

[0051] By adopting the above technical scheme, the relationship between the thickness and pore structure of the alkaline water electrolysis membrane can be further regulated, and the small pore size and high pore density structure of the alkaline water electrolysis membrane can be optimized, which is beneficial for the alkaline water electrolysis membrane to have both high air tightness and low resistance.

[0052] Optionally, the alkali absorption rate Q of the alkaline water electrolysis membrane is 70%-90%, and the alkali absorption rate Q is calculated by the following formula: Q=(M1-M0) / M0, wherein M1 is the mass of the alkaline water electrolysis membrane per unit area in a saturated wet state after being immersed in a 30wt% KOH solution for 4 hours at 90°C, and its unit is g; M0 is the mass of the alkaline water electrolysis membrane per unit area in a dry state, and its unit is g.

[0053] By adopting the above technical solution, the alkali absorption rate of the alkaline water electrolysis membrane has a great influence on the ion conductivity of the alkaline water electrolysis membrane. The higher the alkali absorption rate, the more effective ion transfer pore flow channel volume of the alkaline water electrolysis membrane, and the resistance of the alkaline water electrolysis membrane decreases accordingly, that is, the ion conductivity of the alkaline water electrolysis membrane increases accordingly. Of course, too high an alkali absorption rate is also likely to cause gas crossover problems, so the alkali absorption rate data is preferably controlled to be 70%-90%.

[0054] Optionally, the tensile strength of the alkaline water electrolysis membrane is greater than or equal to 15 MPa, including but not limited to any point value among 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 50 MPa or a range value between any two of them.

[0055] Optionally, at 0.5 MPa, the air permeability of the alkaline water electrolysis membrane is less than or equal to 10 L / min / cm 2 , including but not limited to 1L / min / cm 2 , 2L / min / cm 2 、3L / min / cm 2 、5L / min / cm 2 、6L / min / cm 2 、8L / min / cm 2 、10L / min / cm 2 Any point value in or any range of values ​​between them.

[0056] Optionally, after being immersed in water at 100° C. for 15 minutes, the area change rate of the alkaline water electrolysis membrane is less than or equal to 3%, including but not limited to any point value of 1%, 2%, 3% or any range value between the two.

[0057] Optionally, in a 30 wt% KOH solution at 90°C, the initial surface resistance of the alkaline water electrolysis membrane is less than or equal to 200 mΩ·cm 2 , including but not limited to 30mΩ·cm 2 , 50mΩ·cm 2 、80mΩ·cm 2 、90mΩ·cm 2 , 100mΩ·cm 2 、110mΩ·cm 2 , 120mΩ·cm 2 Any point value in or any range of values ​​between them.

[0058] In the present application, the tensile strength of the diaphragm is measured by a universal tensile tester at 25° C. and 50% RH; the air permeability is measured under the condition that the pressure difference on both sides of the diaphragm is 0.5 MPa.

[0059] In a second aspect, the present application provides a process for preparing an alkaline water electrolysis membrane, comprising the following process steps:

[0060] S1. preparing a casting solution, mixing a high molecular weight polymer, an inorganic hydrophilic particle, a pore-forming agent and a solvent system in a proportion to obtain a casting solution; in the casting solution, the total mass proportion of the high molecular weight polymer and the inorganic hydrophilic particle is 15wt%-25wt%, the added mass ratio of the high molecular weight polymer and the inorganic hydrophilic particle is 1:1-1:9, the mass proportion of the pore-forming agent is 2wt%-5wt%, the surface tension of the pore-forming agent is less than or equal to 30dyne / cm, and the solvent system includes a first good solvent and a first poor solvent, and the mass proportion of the first good solvent is 80wt%-90wt%;

[0061] S2, casting, casting the casting liquid onto the porous carrier to form a coating film;

[0062] S3, pre-gelling, placing the coated film in a pre-gelling bath for pre-gelling to obtain a gel film, wherein the pre-gelling bath comprises a second good solvent and a second poor solvent, and the mass proportion of the second good solvent is 70wt%-80wt%, the temperature of the pre-gelling bath is 40°C-90°C, and the pre-gelling treatment time is 1-3s;

[0063] S4, phase separation solidification, placing the gel film in a phase separation bath to completely phase-solidify the casting liquid to obtain a solidified film, wherein the phase separation bath comprises a third good solvent and a third poor solvent, and the mass proportion of the third good solvent is 5%-15%, and the temperature of the phase separation bath is 10°C-15°C lower than the temperature of the pre-gel bath;

[0064] S5, post-treatment, washing and drying the solidified film to obtain a diaphragm.

[0065] By adopting the above technical scheme, when preparing the alkaline water electrolysis diaphragm, the first step is to prepare the casting liquid. This application controls the mass ratio of the high molecular polymer, inorganic hydrophilic particles, pore-forming agent and solvent in the casting liquid, so that the total solid content of the casting liquid is relatively low, and the content of the polymer component in the solid content is very low, so the total porosity is relatively high after the final curing, and there are a large number of ion transfer channels to ensure that the final diaphragm has a lower resistance. The solvent system obtained by compounding a good solvent and a poor solvent is specially used, and the proportion of the good solvent in the solvent system is controlled to be 80-90wt%. On the one hand, it can ensure that the high molecular polymer is completely dissolved, and on the other hand, a small amount of poor solvent introduced can make the casting liquid in a slightly unstable state, reducing the difficulty of phase separation of the casting liquid.

[0066] The pore-forming agent with low surface tension can promote the subsequent pre-gel and phase-separation solidification stages, and the exchange rate between the components of the casting liquid and the external substances is fast. In the pre-gel stage, the rapid material exchange combined with the slightly unstable casting liquid state can promote the generation of a large number of phase-separation cores in the casting liquid. In the phase-separation solidification stage, a large number of phase-separation cores generated in the pre-gel stage cooperate with the rapid material exchange between the casting liquid and the phase-separation bath to ensure the rapid phase-separation solidification of the diaphragm. The solvent-rich phases do not have sufficient time to approach each other and merge, and naturally it is not easy to form a macroporous structure. Therefore, the composite solvent system, low solid content, low high molecular weight polymer content, and low surface tension pore-forming agent in the casting liquid in this application are indispensable to form the desired small pore size + high pore density structure.

[0067] In the second step of the present application, the method for controlling the thickness during the casting process to form the coating film can be to use an immersion-coordinated scraper, or to immerse and coordinate the roller spacing, or two extrusion heads can respectively control the polymer thickness on both sides and attach it to the support. The present application does not impose any restrictions on this.

[0068] The temperature of the third step pre-gel treatment of the present application is controlled to a relatively high 40-90°C, which can reduce the viscosity of the casting liquid to further increase the speed of material exchange, thereby cooperating with the casting liquid, which is not very stable, to make the pre-gel bath penetrate into the entire membrane more quickly, and because the pre-gel bath contains a relatively high proportion of good solvents, only pre-gel nucleation rather than rapid phase separation and solidification occurs, and it is therefore not easy to introduce a dense cortical structure on the surface of the diaphragm; subsequently, in the fourth step of the phase separation bath treatment, the phase separation bath is basically a non-solvent, so the phases are separated very quickly after the material exchange, and preliminary gel nucleation has already occurred in the pre-gel step, and therefore, the phase separation bath mainly serves to promote further phase separation and solidification, which can also avoid the introduction of a surface cortical structure.

[0069] In particular, the temperature of controlling phase separation solidification in the present application is lower than the pre-gel temperature, and the reason for reducing the temperature is that, as mentioned above, it is generally believed that the higher the temperature, the lower the viscosity of the casting solution, the smaller the permeation resistance, the faster the material exchange between the membrane and the phase separation bath, and the faster the phase separation, the easier it is to produce the small pore structure required for the present application. However, the inventors of the present application unexpectedly found that for the system of the present application, within a certain temperature range, in the phase separation solidification stage, appropriately reducing the temperature can obtain the required small pore structure. This may be due to the fact that, as the temperature increases, the viscosity of the casting solution is indeed lower and lower, but its trend of change is more and more moderate. In other words, within a certain and higher temperature range, although the viscosity changes, the range of change is not large. Correspondingly, for the special composite solvent system casting solution of the present application, within this temperature range, as the temperature decreases, the solubility of the polymer decreases, and this can also promote the phase separation. Therefore, although the temperature in the phase separation and curing stage is lower than that in the pre-gel bath, it is not suitable to be lower than 15°C to ensure that the casting liquid still has a low viscosity for rapid material exchange, and the temperature difference is at least 10°C to ensure that the solubility of the polymer in the casting liquid, which is a composite solvent system, is not too high. The combination of the two can ensure that the system can quickly separate into phases, thereby obtaining a special microscopic pore structure with small pore size and high porosity.

[0070] Optionally, the high molecular weight polymer includes a molecular weight M w The low molecular weight component and molecular weight M are 20,000-80,000 w The high molecular weight component is 150,000-200,000; the mass proportion of the high molecular weight component in the high molecular weight polymer is 5wt%-15wt%.

[0071] By adopting the above-mentioned technical scheme, in combination with the special compound solvent system of the present application, and the special high-temperature pre-gel and low-temperature phase separation and solidification preparation process, the present application also specifically selects a high- and low-molecular-weight blended polymer system. This is because low-molecular-weight polymers are more easily dissolved, resulting in difficulty in phase separation, and the strength of the resulting diaphragm is relatively low; while high-molecular-weight polymers have better mechanical properties, but have high viscosity and are not easy to form films.

[0072] In the preparation process system of the present application, the high molecular weight component with a relatively low proportion can, on the one hand, prevent the casting liquid from being difficult to completely dissolve, and on the other hand, prevent the viscosity of the casting liquid from being too high, which makes it difficult to quickly exchange substances and form nuclei in the pre-gel stage. On the other hand, it can ensure that the phase solidification stage is rapidly phase-separated and solidified as the temperature decreases to form further phase-separated solidification nuclei and promote the overall phase solidification of the casting liquid.

[0073] Optionally, the inorganic hydrophilic particles have a D 50It is 0.1μm-1.5μm, including but not limited to any point value among 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm or any range value between two of them.

[0074] Optionally, the pore former is selected from at least one of methanol, ethanol, propanol, n-butanol, isobutanol, hexafluoroisopropanol or trifluoroethanol.

[0075] Optionally, a water-soluble inorganic salt having a weight percentage of 1 wt% to 3 wt% is further added to the casting solution, and the water-soluble inorganic salt is selected from at least one of calcium chloride, magnesium chloride and sodium chloride.

[0076] By adopting the above technical scheme, the water-soluble inorganic salt can cooperate with the compound solvent system to further improve the instability of the casting solution, thereby promoting the gel nucleation in the pre-gel step. On the other hand, the addition of the water-soluble inorganic salt can reduce the surface tension of the casting solution to a certain extent, and cooperate with the pore-forming agent to make the casting solution have a faster material exchange ability. More importantly, the addition of the inorganic salt can change the concentration difference between the casting solution and the pre-gel bath and the phase separation bath, thereby having a further driving force for material exchange.

[0077] Optionally, the first good solvent, the second good solvent and the third good solvent are each independently selected from at least one of butyl lactate, dimethyl sulfoxide, dimethylformamide, caprolactam, methyl acetate, ethyl acetate, N-ethylpyrrolidone, dimethylacetamide and N-methylpyrrolidone, and the first poor solvent, the second poor solvent and the third poor solvent are all water.

[0078] The specific solvent system is helpful to further ensure that the casting solution has a suitable viscosity, thereby further ensuring that the prepared diaphragm has a specific pore structure.

[0079] In a third aspect, the present invention provides an alkaline water electrolysis device, which adopts the following technical solution:

[0080] An alkaline water electrolysis device comprises the alkaline water electrolysis diaphragm as described above.

[0081] The alkaline water electrolysis diaphragm provided in the present application is used in an alkaline water electrolysis device. Under working conditions such as circulation of electrolyte and gas shock generated by electrolysis, it has both high air tightness and low resistance, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0082] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0083] Figure 1 This is a schematic diagram of a scanning electron microscope (SEM) of a cross section of the alkaline water electrolysis diaphragm obtained in Example 1, with a magnification of 100 times;

[0084] Figure 2 This is a schematic diagram of a scanning electron microscope (SEM) of one side surface of the alkaline water electrolysis membrane obtained in Example 1, with a magnification of 10K times.

[0085] Figure 3 This is a schematic diagram of a scanning electron microscope (SEM) of the other side surface of the alkaline water electrolysis membrane obtained in Example 1, with a magnification of 10K times.

[0086] Figure 4 The pore size distribution of the alkaline water electrolysis membrane obtained in Example 1 is calculated by the NLDFT method in the BET test and the pore size distribution curve is obtained by fitting. DETAILED DESCRIPTION

[0087] The alkaline water electrolysis membrane and its method and application will be further described below by the following specific examples. However, it will be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0088] Example 1

[0089] S1. Preparation of a casting solution: a high molecular weight polymer, inorganic hydrophilic particles, a pore-forming agent, a water-soluble inorganic salt and a solvent system are mixed according to a mass ratio to obtain a casting solution. Specifically, based on 100 parts by weight of the casting solution, the casting solution includes the following components in parts by weight:

[0090] 4 parts of high molecular weight polymer, of which 0.4 parts of high molecular weight component and 3.6 parts of low molecular weight component are added, that is, the high molecular weight polymer is composed of molecular weight M w =50,000 low molecular weight components and molecular weight M w =180,000 high molecular weight components are blended, and the mass proportion of the high molecular weight component in the high molecular weight polymer is 10wt%; in this embodiment, the high molecular weight component and the low molecular weight component are both polyethersulfone;

[0091] 16 parts of inorganic hydrophilic particles, that is, the addition mass ratio of high molecular weight polymer to inorganic hydrophilic particles is 1:4, and the total solid content is 20wt%; in this embodiment, the inorganic hydrophilic particles are selected from Mel Chemical E101 (equivalent to D 50 =0.8 μm);

[0092] 3 parts of pore-forming agent. In this embodiment, the pore-forming agent is ethanol, and its surface tension is 22.3 dyne / cm@20°C;

[0093] 2 parts of water-soluble inorganic salt, in this embodiment, the water-soluble inorganic salt is sodium chloride;

[0094] The solvent system has a total of 75 parts, and the solvent system specifically includes a first good solvent with a mass proportion of 85wt% and a first poor solvent with a mass proportion of 15wt%. In this embodiment, the first good solvent is N-ethylpyrrolidone, and the first poor solvent is water.

[0095] S2, casting, casting the casting liquid onto the porous carrier to form a coating film; in this embodiment, a PPS woven mesh with a thickness of about 100 μm and 160 mesh is used as the porous carrier, and the porous carrier is immersed in the casting liquid, and the thickness of the casting liquid on both sides is controlled by rolling on both sides and controlling the distance between the rollers.

[0096] S3, pregel, placing the coated film in a pregel bath for pregelation to obtain a gel film, the pregel temperature is 70°C, and the pregel treatment time is 2s; in this embodiment, the pregel bath includes 75wt% of the second good solvent and 25wt% of the second poor solvent, and the second good solvent is N-ethylpyrrolidone, and the second poor solvent is water.

[0097] S4, phase separation solidification, placing the gel film in a phase separation bath to allow the casting liquid to completely phase separate and solidify to obtain a solidified film, and the temperature of the phase separation bath is 12°C lower than the temperature of the pre-gel bath. Specifically, the temperature of the phase separation bath is 58°C; in this embodiment, the phase separation bath includes a third good solvent with a mass proportion of 10wt% and a third poor solvent with a mass proportion of 90wt%, and the third good solvent is N-ethylpyrrolidone, and the second poor solvent is water.

[0098] S5, post-treatment, washing the cured film 3-5 times and drying to obtain a separator. The rest is detailed in the table below.

[0099] Example 2

[0100] The main difference between Example 2 and Example 1 is that the formula of the casting liquid and various process parameters are adjusted. Specifically, this embodiment reduces the proportion of high molecular weight components in the casting liquid and reduces the total proportion of polymers, and adds inorganic hydrophilic particles with larger particle sizes, so that the diaphragm tends to form a large-pore flow channel structure. The higher content of good solvent in the pregel bath, the longer pregel treatment time, and the higher pregel bath temperature all make the casting liquid not only produce pregel nucleation in the pregel stage, but also promote phase separation to a certain extent, and the process of fusion and expansion of the size of the polymer-rich phase and the solvent-rich phase. In addition, the higher proportion of good solvent in the phase separation and curing stage slows down the phase separation and curing speed, which is also conducive to the diaphragm to produce a larger-sized pore flow channel structure. In this application, the inorganic hydrophilic particles are selected from Mel Chemical's E20 (equivalent to D 50 =1.5μm) zirconium dioxide. See the table below for details.

[0101] Example 3

[0102] The main difference between Example 3 and Example 1 is that the formula of the casting liquid and various process parameters are adjusted. Specifically, this embodiment has a higher total polymer ratio and the addition of smaller particle size inorganic hydrophilic particles, so that the diaphragm tends to form a small-sized pore flow channel structure. The addition of more pore formers in the casting liquid and the lower proportion of good solvents in the solvent system reduce the difficulty of phase separation of the casting liquid, as well as the lower proportion of good solvents in the pre-gel bath in the pre-gel step, and the lower pre-gel temperature and time, which avoid further processes other than nucleation during the pre-gel treatment. The lower proportion of good solvents in the phase separation bath in the phase separation and curing step is conducive to the rapid phase separation of the casting liquid. The inorganic hydrophilic particles are selected from UEP zirconium dioxide of DKK (made by First Rare Element Chemical Industry) with a nominal D50 of 0.4-0.7μm. See the table below for details.

[0103] Embodiment 4-5

[0104] The main difference between Example 4-5 and Example 1 is that by adjusting the proportion of high molecular weight components in the casting solution formula to a higher level and matching the poor solvent in the solvent system to a higher level, the stability of the casting solution is reduced, and the pre-gel treatment and phase separation solidification steps are matched to reduce the phase separation uniformity, thereby reducing the uniformity of the pore structure on the surface of the diaphragm. See the table below for details.

[0105] Example 6

[0106] The main difference between Example 6 and Example 1 is that the roller spacing is controlled in step S2 to obtain a lower thickness separator, and in addition, during phase separation curing, the temperature difference between the phase separation bath and the pre-gel bath is 10° C. See the table below for details.

[0107] Example 7

[0108] The main difference between Example 7 and Example 1 is that the roller spacing is controlled in step S2 to obtain a thicker separator, and in addition, during phase separation curing, the temperature difference between the phase separation bath and the pre-gel bath is 15° C. See the table below for details.

[0109] Comparative Example

[0110] Comparative Example 1

[0111] The main difference between Comparative Example 1 and Example 1 is that, as far as the casting solution is concerned, Comparative Example 1 has the same solid content as Example 1, but has a lower amount of polymer added (the mass ratio of polymer to inorganic hydrophilic particles added is 1:19) and the particle size of the inorganic hydrophilic particles is larger, and specifically, EP type zirconium dioxide of DKK (First Rare Element Chemical Industry) with a nominal D50 of 1.5-2.5 μm is selected. In addition, all polymers are low molecular weight components that are easy to dissolve and difficult to separate, and no high molecular weight components are added, and the solvent system is all good solvents, and no poor solvents are added, so the casting solution has a higher stability. In addition, no low surface tension pore-forming agent that promotes material exchange is added to the casting solution, and no inorganic salt is added. In terms of preparation process parameters, in the pre-gel treatment process of Comparative Example 1, a higher pre-gel treatment temperature (90°C) and a longer pre-gel time (5s) were used to allow the pre-gel bath to exchange substances with the casting solution. However, due to the higher stability of the casting solution, it was more diluted by the pre-gel bath rather than nucleated pre-phase separation; in the phase separation and curing stage, a phase separation bath with a higher proportion of good solvent was used for phase separation treatment. Finally, a diaphragm with a larger pore size and higher porosity was obtained.

[0112] Comparative Example 2

[0113] The main difference between Comparative Example 2 and Example 1 is that, as far as the casting liquid is concerned, although Comparative Example 2 has the same solid content as Example 1, it has a higher amount of polymer added (the mass ratio of polymer to inorganic hydrophilic particles is 3:2) and the particle size of the inorganic hydrophilic particles is smaller, specifically the AT-R50 model zirconium dioxide with an average particle size of 50nm of Zhejiang Zhiti Nano Micro Company. In addition, all polymers are high molecular weight components that are difficult to dissolve and easy to phase separate, and no low molecular weight components are added. In addition, the proportion of good solvents in the solvent system is slightly lower (accounting for 75wt%), so the stability of the casting liquid is already low. In addition, the amount of low surface tension pore-forming agent added to promote material exchange in the casting liquid is 6 parts, and the amount of inorganic salt added is 5 parts. In terms of preparation process parameters, the pre-gel process of Comparative Example 2 is the same as that of Example 1, but the phase separation and curing process adopts a lower proportion of good solvents in the phase separation bath and a larger temperature difference to promote the rapid phase separation and curing of the casting liquid. Finally, a diaphragm with a smaller pore size and a lower porosity is obtained.

[0114] Table 1 Process parameters of various embodiments and comparative examples

[0115]

[0116]

[0117] Performance tests and parameters

[0118] The performance of the diaphragms prepared in the embodiments and comparative examples was tested using the aforementioned test methods and recorded in the following table:

[0119] Table 2 Performance parameters of various embodiments and comparative examples

[0120]

[0121]

[0122] in conclusion

[0123] By comparing the solutions and test data of Example 1 and Comparative Examples 1-2, it is not difficult to find that the specific technical solution of high porosity, small pore size and high pore density in the present application can not only make the diaphragm have higher anti-gas cross performance, but also have lower resistance.

[0124] By comparing the schemes and test data of Example 1 and Example 2, it is not difficult to find that in the pore size-pore volume distribution curve of the diaphragm in Example 2, the highest peak is located in the region of 10-100 nm, that is, compared with Example 1, the diaphragm of Example 2 has a large number of pore flow channel structures with a size of 10-100 nm. This improves the electrolytic performance of the diaphragm to a certain extent and reduces the resistance, but it is accompanied by a decrease in its air tightness and a slight decrease in the anti-gas cross performance, of course, it is still significantly better than Comparative Examples 1-2.

[0125] By comparing the schemes and test data of Example 1 and Example 3, it is not difficult to find that in the pore size-pore volume distribution curve of the diaphragm in Example 3, the highest peak is still located in the region of 1-10 nm, but the pore flow channels in this region account for a high proportion, which means that Example 3 has a large number of pore flow channel structures with a size of 1-10 nm. This makes the diaphragm have particularly excellent anti-gas crossover performance, but the slightly lower porosity and smaller pore size make the resistance of the diaphragm slightly increased.

[0126] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0127] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An alkaline water electrolysis membrane, comprising a porous carrier and a porous hydrophilic layer disposed on both sides of the porous carrier, wherein the porous hydrophilic layer comprises a high molecular polymer and inorganic hydrophilic particles, and the porous hydrophilic layer at least partially penetrates into the pore structure of the porous carrier, characterized in that: The thickness of the alkaline water electrolysis membrane is 150μm-600μm, and the maximum thickness ratio is 20kPa / 100μm-200kPa / 100μm, and the maximum thickness ratio is the ratio of the IPA bubbling point corresponding to the maximum pore size of the membrane to the thickness of the membrane; the porosity of the alkaline water electrolysis membrane is 45%-75%, and the water contact angle is less than or equal to 80°.

2. The alkaline water electrolysis membrane according to claim 1, characterized in that: In the pore size-pore volume distribution curve of the alkaline water electrolysis membrane, the abscissa is the pore size and is sorted from small to large, and the ordinate is the change in pore volume under a unit pore size change. The pore size-pore volume distribution curve satisfies at least one of the following conditions: (1) The highest peak is located in the 1nm-10nm pore size region; (2) The peak intensity of the highest peak in the pore size region of 10 nm to 100 nm is greater than the peak intensity of the highest peak in the pore size region of more than 100 nm.

3. The alkaline water electrolysis membrane according to claim 2, characterized in that: In the pore size-pore volume distribution curve of the alkaline water electrolysis membrane, the peak intensity ratio of the highest peak in the pore size region of 1nm-10nm to the highest peak in the pore size region of 10nm-100nm is 1.5-10.

4. The alkaline water electrolysis membrane according to claim 2, characterized in that: In the pore size-pore volume distribution curve of the alkaline water electrolysis membrane, the peak intensity ratio of the highest peak in the pore size region of 1 nm-10 nm to the highest peak in the pore size region of 0-1 nm is greater than or equal to 5.

5. The alkaline water electrolysis membrane according to any one of claims 1 to 4, characterized in that: The ratio of the SEM median pore size to the SEM average pore size of the surface pores of the alkaline water electrolysis membrane is 0.7-1.2; And / or, the surface pores of the alkaline water electrolysis membrane have a pore area percentage of 20%-60% on the surface of the alkaline water electrolysis membrane.

6. The alkaline water electrolysis membrane according to claim 1, characterized in that: On the surface of the alkaline water electrolysis membrane, the average value of the minimum distance between adjacent pore structures is 100nm-500nm.

7. The alkaline water electrolysis membrane according to claim 6, characterized in that: The ratio of the SEM particle size of the inorganic hydrophilic particles to the average value of the minimum distance between adjacent pore structures is 0.1-1.

5.

8. The alkaline water electrolysis membrane according to claim 1, characterized in that: The ratio of the average pore size of the PMI of the alkaline water electrolysis membrane to the thickness of the alkaline water electrolysis membrane is less than or equal to 10 nm / 100 μm.

9. The alkaline water electrolysis diaphragm according to claim 1, characterized in that: The alkali absorption rate Q of the alkaline water electrolysis membrane is 70%-90%, and the alkali absorption rate Q is calculated by the following formula: Q=(M1-M0) / M0, wherein M1 is the mass of the alkaline water electrolysis membrane per unit area in a saturated wet state after being immersed in a 30wt% KOH solution for 4 hours at 90°C, and its unit is g; M0 is the mass of the alkaline water electrolysis membrane per unit area in a dry state, and its unit is g.

10. The alkaline water electrolysis membrane according to claim 1, characterized in that: The alkaline water electrolysis membrane also satisfies at least one of the following conditions: (1) The tensile strength of the alkaline water electrolysis diaphragm is greater than or equal to 15 MPa; (2) Under 0.5 MPa conditions, the air permeability of the alkaline water electrolysis membrane is less than or equal to 10 L / min / cm 2 ; (3) After being immersed in water at 100° C. for 15 min, the area change rate of the alkaline water electrolysis membrane is less than or equal to 3%; (4) At 90°C, in a 30wt% KOH solution, the initial surface resistance of the alkaline water electrolysis membrane is less than or equal to 200 mΩ·cm 2 .

11. The alkaline water electrolysis membrane according to claim 1, characterized in that: The high molecular polymer is selected from at least one of polysulfone, polyethersulfone and polyphenylsulfone; And / or, the inorganic hydrophilic particles are selected from at least one of zirconium oxide, titanium oxide, bismuth oxide, cerium oxide, magnesium oxide, zirconium hydroxide, titanium hydroxide, bismuth hydroxide, cerium hydroxide, magnesium hydroxide and barium sulfate.

12. A process for preparing an alkaline water electrolysis membrane according to any one of claims 1 to 11, characterized in that: The process steps include: S1. preparing a casting solution, mixing a high molecular weight polymer, an inorganic hydrophilic particle, a pore-forming agent and a solvent system in a proportion to obtain a casting solution; in the casting solution, the total mass proportion of the high molecular weight polymer and the inorganic hydrophilic particle is 15wt%-25wt%, the added mass ratio of the high molecular weight polymer and the inorganic hydrophilic particle is 1:1-1:9, the mass proportion of the pore-forming agent is 2wt%-5wt%, the surface tension of the pore-forming agent is less than or equal to 30dyne / cm, and the solvent system includes a first good solvent and a first poor solvent, and the mass proportion of the first good solvent is 80wt%-90wt%; S2, casting, casting the casting liquid onto the porous carrier to form a coating film; S3, pre-gelling, placing the coated film in a pre-gelling bath for pre-gelling to obtain a gel film, wherein the pre-gelling bath comprises a second good solvent and a second poor solvent, and the mass proportion of the second good solvent is 70wt%-80wt%, the temperature of the pre-gelling bath is 40°C-90°C, and the pre-gelling treatment time is 1-3s; S4, phase separation solidification, placing the gel film in a phase separation bath to completely phase-solidify the casting liquid to obtain a solidified film, wherein the phase separation bath comprises a third good solvent and a third poor solvent, and the mass proportion of the third good solvent is 5%-15%, and the temperature of the phase separation bath is 10°C-15°C lower than the temperature of the pre-gel bath; S5, post-treatment, washing and drying the solidified film to obtain a diaphragm.

13. The process for preparing an alkaline water electrolysis membrane according to claim 12, characterized in that: The high molecular weight polymer includes a molecular weight M w The low molecular weight component and molecular weight M are 20,000-80,000 w The high molecular weight component is 150,000-200,000; the mass proportion of the high molecular weight component in the high molecular weight polymer is 5wt%-15wt%.

14. The process for preparing an alkaline water electrolysis membrane according to claim 12, characterized in that: The inorganic hydrophilic particles have a D 50 0.1μm-1.5μm; And / or, the pore former is selected from at least one of methanol, ethanol, propanol, n-butanol, isobutanol, hexafluoroisopropanol or trifluoroethanol.

15. The process for preparing an alkaline water electrolysis membrane according to claim 12, characterized in that: The casting solution is further added with a water-soluble inorganic salt having a mass percentage of 1wt%-3wt%, and the water-soluble inorganic salt is selected from at least one of calcium chloride, magnesium chloride and sodium chloride.

16. The process for preparing an alkaline water electrolysis membrane according to claim 12, characterized in that: The first good solvent, the second good solvent and the third good solvent are each independently selected from at least one of butyl lactate, dimethyl sulfoxide, dimethylformamide, caprolactam, methyl acetate, ethyl acetate, N-ethylpyrrolidone, dimethylacetamide and N-methylpyrrolidone, and the first poor solvent, the second poor solvent and the third poor solvent are all water.

17. An alkaline water electrolysis device, characterized in that: The alkaline water electrolysis device comprises the alkaline water electrolysis membrane as described in any one of claims 1-11.